Virological patterns of HCV patients with failure to interferon‐free regimens. Issue 5 (1st February 2018) - Starace, Mario; Minichini, Carmine; De Pascalis, Stefania; Macera, Margherita; Occhiello, Laura; Messina, Vincenzo; Sangiovanni, Vincenzo; Adinolfi, Luigi E.; Claar, Ernesto; Precone, Davide; Stornaiuolo, Gianfranca; Stanzione, Maria; et al.
Abstract : The study characterized the virological patterns and the resistance‐associated substitutions (RASs) in patients with failure to IFN‐free regimens enrolled in the real‐life setting. All 87 consecutive HCV patients with failed IFN‐free regimens, observed at the laboratory of the University of Campania, were enrolled. All patients had been treated with DAA regimens according to the HCV genotype, international guidelines, and local availability. Sanger sequencing of NS3, NS5A, and NS5B regions was performed at failure by home‐made protocols. Of the 87 patients enrolled, 13 (14.9%) showed a misclassified HCV genotype, probably causing DAA failure, 16 had been treated with a sub‐optimal DAA regimen, 19 with a simeprevir‐based regimen and 39 with an optimal DAA regimen. A major RAS was identified more frequently in the simeprevir regimen group (68.4%) and in the optimal regimen group (74.4%) than in the sub‐optimal regimen group (56.3%). The prevalence of RASs in NS3 was similar in the three groups (30.8‐57.9%), that in NS5A higher in the optimal regimen group (71.8%) than in the sub‐optimal regimen group (12.5%, P < 0.0001) and in the simeprevir regimen group (31.6%, P < 0.0005), and that in NS5B low in all groups (0‐25%). RASs in two or more HCV regions were more frequently identified in the optimal regimen group (46.6%) than in the simeprevir‐based regimen group (31.6%) and sub‐optimal regimen group (18.7%). In our real‐life population the prevalence of RASs was high, especially in NS3 and NS5A and in those treated with suitable DAA regimens.